KATAKAN TIDAK UNTUK KORUPSI - Asep Tapip Yani (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2005)
Many people have been addressing and expressing anticorruption. Even, the government always campaigns for the anticorruption movements. However, the corruption itself does not decrease. Corruption has been a lifestyle, and for somebody it has become a modern culture. This assumption seems to be mass-assumption as community assumption.. That is why corruption has become a hard thing to solve. So, how can we solve the corruption problem?What kind of efforts should we take for it? Where should we start to solve it? And what are the priority steps to do to construct a good governance and clean government?Corruptive acts work systematically. Corruption has been a model of lifestyle and has destroyed many kinds of life aspects. Corruption is a determinant factor for poverty. It also destroys human and social capital of our nation. Ability to comprehensively formulate what the problems and corruption affect is very important. However, it becomes nothing without arguing alternative solutions to cope with corruption problems. In fact, the implementation of the alternative solution itself often becomes meaningless because of limited persepective. Corruption is often stated only as legal problems. It is not only a legal problem, but more than law problems. It can be political, social, economical, and cultural problems. Thus, we need to find the suitable way to cope with the problems